Abdominal obesity and frailty progression in population across different Cardiovascular-Kidney-Metabolic syndrome stages: a nationwide longitudinal study - Chong Zhang; Cuijun Hao; Weiru Liang; Kun Hu; Tingting Guo; Yi Chen; Meng Ning; Yingwu Liu (Diabetology & Metabolic Syndrome)
Abstract Background Abdominal obesity, assessed via the body roundness index (BRI), is a critical determinant of health outcomes. This study explores the association between abdominal obesity and frailty progression across different stages of Cardiovascular-Kidney-Metabolic (CKM) syndrome in a nationwide longitudinal cohort. Methods Data were derived from the China Health and Retirement Longitudinal Study, including individuals aged ≥ 45 years. Participants were categorized into early and advanced CKM syndrome stages. The BRI was used to measure abdominal obesity, and frailty was assessed using the frailty index. Results Higher BRI in individuals within early CKM syndrome stages was associated with an increased risk of frailty progression compared to those with advanced stages (adjusted hazard ratio [aHR] 1.30, 95% confidence interval [CI] 1.17–1.45 vs. aHR 1.16, 95% CI 0.96–1.40). High cumulative BRI with advanced CKM stages progression and persistent advanced CKM stages over time also predicted a greater risk of frailty. Furthermore, BRI outperformed body mass index (BMI) in predicting frailty progression after combined with conventional model (area under the curve [AUC] 0.708, 95% CI 0.694–0.722 vs. AUC 0.704, 95% CI 0.690–0.718; P = 0.033). Conclusions Abdominal obesity, indicated by BRI, is a strong predictor of frailty progression, particularly in early CKM stages. High cumulative BRI, along with advanced CKM progression and persistent advanced CKM stages, further increases frailty risk. Notably, BRI outperforms BMI in enhancing conventional frailty prediction models. These findings underscore the importance of monitoring abdominal obesity in early CKM stages to mitigate future frailty risk. Graphical Abstract